2019
DOI: 10.20471/acc.2019.58.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Peritumoral Brain Edema with Morphological Characteristics and Ki67 Proliferative Index in Resected Intracranial Meningiomas

Abstract: SUMMARY The aim of the study was to analyze correlation between morphological characteristics of intracranial meningiomas and Ki67 labeling index (Ki67 LI), and their influence on peritumoral brain edema (PTBE). There were 41 consecutive patients with intracranial meningiomas surgically treated at the Department of Neurosurgery, Zenica Cantonal Hospital, Zenica, Bosnia and Herzegovina, during the period from January 2010 to December 2015. We reviewed clinical data including patient age, gender, magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
(49 reference statements)
0
19
0
1
Order By: Relevance
“…P value was calculated to be 0.014 indicating strong correlation between PTBE and Ki67 index (Table 4). [31]. We also found no statistically significant relationship between the tumor volume and PTBE and/or gender, the different results encountered in multiple papers may further enhance the hypothesis that other multiple factors rather than volume that contribute to PTBE development.…”
Section: Tumor Volume Ptbe and Ki67 Indexmentioning
confidence: 48%
See 1 more Smart Citation
“…P value was calculated to be 0.014 indicating strong correlation between PTBE and Ki67 index (Table 4). [31]. We also found no statistically significant relationship between the tumor volume and PTBE and/or gender, the different results encountered in multiple papers may further enhance the hypothesis that other multiple factors rather than volume that contribute to PTBE development.…”
Section: Tumor Volume Ptbe and Ki67 Indexmentioning
confidence: 48%
“…Kim B-W et al, found in their study on 86 patients with meningiomas that higher Ki-67 antigen indices lead to a higher frequency of PTBE [12], which is in agreement with our findings. Other studies also showed a strong correlation between PTBE and Ki67 indices [24] [30] [31] [42] but due to limitations and multiple factors that influence PTBE, further research on larger group of patients and longer follow up periods may be required to conclusively determine the definite relationship.…”
Section: Tumor Volume Ptbe and Ki67 Indexmentioning
confidence: 99%
“…PTBE is a consequence of high rates of angiogenesis in rapidly growing tumors and tissue hypoxia. 12 PTBE has also been associated with increased risk of recurrence, 36 increased Ki-67 proliferative index, 37 and worse postoperative cognitive functioning 38 and KPS. 39 Meningiomas are highly vascularized tumors and, thus, potentially amenable to antiangiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 While a few studies have shown significant findings correlating PTBE with histological grade especially of WHO grade II and grade III and uncommon variants of WHO grade I meningiomas. [26][27][28][29][30] Moreover, number of studies also showed that of the several types of WHO grade I meningiomas, meningothelial, transitional and secretory variants had a higher tendency to produce PTBE. 27,29,[31][32][33] Further, in this study after a yearly follow up for a period of 4 years it was found that 10 cases recurred.…”
Section: Discussionmentioning
confidence: 99%